1999
DOI: 10.1046/j.1464-410x.1999.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of homocysteine and copper markedly inhibits the relaxation of rabbit corpus cavernosum: new risk factors for angiopathic erectile dysfunction?

Abstract: HCy inhibited NO-mediated cavernosal smooth muscle relaxation, an effect that was potentiated by copper and reversed by superoxide dismutase or catalase. It is therefore proposed that the effect of HCy on cavernosal smooth muscle relaxation is mediated by an interaction between NO and superoxide anions. Moreover, HCy may constitute a new risk factor for angiopathic ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 21 publications
4
44
0
3
Order By: Relevance
“…154 Thus it was found that Hcy interacts with copper to Hcy impairs endotheliumdependent relaxation in the rabbit cavernosum. 152,153 This inhibitory effect was reversed by both SOD and catalase, suggesting both O 2 KÀ and H 2 O 2 mediated this effect of Hcy and copper together. In a more recent in vivo study it was demonstrated that administration of penicillamine, a copper chelator, reversed the impairment of endothelium-dependent relaxation, O 2 KÀ formation and NADPH oxidase upregulation in both cavernosal and arterial tissue elicited by experimental HHC.…”
Section: Ros Andmentioning
confidence: 99%
See 1 more Smart Citation
“…154 Thus it was found that Hcy interacts with copper to Hcy impairs endotheliumdependent relaxation in the rabbit cavernosum. 152,153 This inhibitory effect was reversed by both SOD and catalase, suggesting both O 2 KÀ and H 2 O 2 mediated this effect of Hcy and copper together. In a more recent in vivo study it was demonstrated that administration of penicillamine, a copper chelator, reversed the impairment of endothelium-dependent relaxation, O 2 KÀ formation and NADPH oxidase upregulation in both cavernosal and arterial tissue elicited by experimental HHC.…”
Section: Ros Andmentioning
confidence: 99%
“…150 Although the angiopathic effect of Hcy is thought to be mediated by the auto-oxidation of Hcy to form O 2 À and H 2 O 2, 151 Hcy alone may not be vasculopathic. Hcy at up to 1 mM, Hcy has no effect on the relaxation of cavernosal or arterial tissue, in vitro, 152,153 indicating the involvement of another factor, in vivo. The generation of O 2 KÀ from Hcy is augmented by copper ions via Fenton and HaberWeiss reactions.…”
Section: Ros Andmentioning
confidence: 99%
“…Major risk factors for vascular diseases, including hypercholesterolemia , atherosclerosis (Khan et al, 1999), and diabetes mellitus (Cartledge et al, 2000;Nangle et al, 2004), can interfere with the intricate vascular mechanisms underlying normal erection, and they are often associated with increased superoxide anion (O 2 . ) formation in the vasculature.…”
mentioning
confidence: 99%
“…3 ED, especially for vasculogenic ED, is a vascular disorder of cavernosal vascular bed. Several clinical trials [4][5][6] and animal experiments 7,8 conducted on ED have demonstrated its close correlation with hcy.…”
Section: Introductionmentioning
confidence: 96%
“…Khan et al reported hcy had an inhibitory effect on endothelium-dependent relaxation and NO formation in rabbit corpus cavernosum and this effect was augmented by copper and reversed by superoxide dismutase or catalase. 8 Demir et al showed that the presence of elevated levels of hcy (>12.1 μmol l −1 ) strongly predicted the occurrence of ED 6 while Al-Hunayan et al demonstrated that 1 μmol l −1 increase of plasma hcy concentration was associated with 2.95 times the odds of ED when compared to control subjects. 4 Wang concluded in a review that hhcy to be "a novel risk factor of ED" and the measurement of plasma hcy might be "added to the ED diagnostic procedure. "…”
Section: Introductionmentioning
confidence: 99%